Solid electrolyte, preparation method and application thereof, and lithium ion battery
Through interlaced multi-layer structure solid electrolyte and specific preparation methods, the problems of insufficient safety and conductivity of liquid electrolytes in lithium-ion batteries are solved, and low impedance, high elongation of break and high first discharge capacity are achieved. Lithium-ion battery.
Patent Information
- Application Number
- CN202310813792.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-04
AI Technical Summary
The liquid electrolytes in existing lithium-ion batteries have safety problems such as flammability, solvent leakage and explosion, and their conductivity is insufficient, which hinders the large-scale commercialization of lithium-ion batteries.
Using a multi-layer structure solid electrolyte with interlaced arrangement, through the interlaced arrangement of polymers and alkali metal salts, combined with inorganic fillers, a solid electrolyte with high conductivity and mechanical properties is formed, and a porous sandwich structure is formed through a specific preparation method. .
It realizes the low impedance, high elongation of break and high first discharge capacity of solid electrolytes, improving the safety and performance of lithium-ion batteries.
Smart Images

Figure CN119275338A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a solid electrolyte, a preparation method and application thereof, and a lithium ion battery. Background Art
[0002] With the growing interest in the commercialization of electric vehicles in power tools, hybrid electric vehicles, and automotive industries, as well as portable devices in daily life, there is a growing focus on the development of high-performance lithium-ion batteries. As one of the key components, electrolyte is very important for the preparation of long-life and high-performance lithium-ion batteries. In most commercial batteries, the electrolyte used is generally an optimized liquid electrolyte with high performance in terms of conductivity. However, liquid electrolytes have performance degradation and safety issues such as leakage of flammable solvents, fire, and explosion, which hinder the large-scale commercialization of lithium-ion batteries. Therefore, it is imperative to study safer and more reliable electrolytes for lithium-ion batteries. In addition, in order to improve the performance and energy density of LIBs, the high demand for new electrolytes needs to be better understood.
[0003] Polymer-based solid electrolytes (SPE) have attracted extensive attention due to their excellent properties such as safety, mechanical properties and flexibility. Ions can move in the space provided by the free volume of the polymer body, so the conductivity may be higher than the glass transition temperature (Tg) of the polymer, at which the polymer molecules can move freely. The current improvement directions are mainly in two aspects: one is to increase the ionic conductivity of the all-solid electrolyte, and the other is to improve the interface contact between the electrolyte and the electrode sheet. In response to these two problems, most of the improvements made so far are focused on the materials used and the manufacturing process, which can be mainly divided into the following categories: 1) Adding inorganic fillers or plasticizers to improve ionic conductivity, and regulating the type and distribution of inorganic fillers; 2) Modifying polymers: grafting, copolymerization, composite, etc.; 3) Optimizing the type of lithium salts and applying new lithium salts or additives; 4) Improving the film-forming process, such as using hot pressing instead of traditional solution film-forming, and the whole process is green and pollution-free. Summary of the invention
[0004] As mentioned above, in view of the defects of the electrolyte, there are few reports in the prior art that focus on improving the morphology and structure of the membrane to reduce impedance. In view of this, the present invention provides a solid electrolyte, a preparation method and application thereof, and a lithium-ion battery.
[0005] According to the first aspect of the present invention, the present invention provides a solid electrolyte, which includes an A layer and a B layer arranged in an alternating manner, wherein the A layer material is different from the B layer material, the A layer material and the B layer material each contain a polymer and an alkali metal salt, and one of the A layer material and the B layer material contains an inorganic filler.
[0006] According to a second aspect of the present invention, the present invention provides a method for preparing a solid electrolyte, wherein the method comprises:
[0007] a) forming a slurry M with a polymer and an alkali metal salt;
[0008] b) forming a slurry N with the polymer, the alkali metal salt and the inorganic filler;
[0009] c) coating slurry M or slurry N into a film and heating until the solvent evaporates; coating another layer of different slurry at a fixed point on the surface of the film, maintaining the fixed position and then scraping the slurry flat, and heating until the solvent evaporates; optionally, repeating the fixed-point coating, fixed-point maintenance and scraping of another layer of slurry and heating until the solvent evaporates as needed; so that the electrolyte includes a staggered multilayer structure.
[0010] According to a third aspect of the present invention, the present invention provides a use of the solid electrolyte described in the present invention or the solid electrolyte prepared by the method described in the present invention in a battery.
[0011] According to a fourth aspect of the present invention, the present invention provides a lithium-ion battery, which is assembled from a solid electrolyte, a positive electrode sheet and a lithium sheet, wherein the solid electrolyte is the solid electrolyte described in the present invention or a solid electrolyte prepared by the method described in the present invention.
[0012] The solid electrolyte of the present invention has the advantages of low impedance, high elongation at break and high initial capacity of the assembled battery.
[0013] The polymer-based solid electrolyte synthesized by the present invention is assembled into a button cell together with a lithium sheet and a lithium iron phosphate positive electrode sheet, and its impedance spectrum at 30-70°C is tested to characterize the impedance and ion diffusion properties of the material. Compared with the control sample of the ordinary single-layer PEO-LiFSI-LLZTO membrane, the Re characterizing the material impedance of the sample of the present invention is reduced from 800Ω to 367Ω. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a SEM image of the surface of the porous sandwich structure all-solid electrolyte of Example 1;
[0015] Figure 2 This is an enlarged SEM image of the pores on the surface of the porous sandwich structure all-solid electrolyte of Example 1;
[0016] Figure 3 This is a SEM image of a cross section of a porous sandwich structure all-solid electrolyte of Example 1;
[0017] Figure 4 The impedance spectrum of the lithium battery based on the porous sandwich structure all-solid electrolyte of Example 1;
[0018] Figure 5 This is the SEM image of the surface of the single-layer all-solid-state electrolyte of Comparative Example 1. DETAILED DESCRIPTION
[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0020] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.
[0021] In the context of this specification, any two or more aspects of the present invention may be arbitrarily combined, and the technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0022] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.
[0023] The present invention relates to the following embodiments.
[0024] The present invention provides a solid electrolyte, which includes an A layer and a B layer arranged in a staggered manner, wherein the A layer material is different from the B layer material, the A layer material and the B layer material each contain a polymer and an alkali metal salt, and one of the A layer material and the B layer material contains an inorganic filler. The solid electrolyte of the present invention has the advantages of low impedance, high elongation at break, high initial capacity of the assembled battery, high ionic conductivity, and good flexibility.
[0025] According to a preferred embodiment of the present invention, preferably, the solid electrolyte and the lithium iron phosphate electrode sheet are assembled into a battery with an initial discharge capacity of 160 mAh g -1 above.
[0026] According to a preferred embodiment of the present invention, the impedance Re of the solid electrolyte is below 500Ω; preferably, the impedance Re of the solid electrolyte at 60°C is 300-500Ω.
[0027] According to a preferred embodiment of the present invention, preferably, the tensile elongation at break of the solid electrolyte is above 100%, preferably 100-150%.
[0028] In the present invention, the thickness of the solid electrolyte can be selected in a wide range. According to a preferred embodiment of the present invention, preferably, the thickness of the solid electrolyte is 900-2000 μm.
[0029] According to a preferred embodiment of the present invention, preferably, the solid electrolyte has a plurality of pores, each of which exists independently and has an irregular shape, and the pores do not penetrate the layer structure of the electrolyte. The solid electrolyte having the above structure has the advantages of high ionic conductivity and good flexibility.
[0030] According to a preferred embodiment of the present invention, the pores preferably have a pore diameter of 1-20 μm.
[0031] According to a preferred embodiment of the present invention, preferably, the holes have filamentous morphology running through them. The solid electrolyte having the above structure has the advantage of good mechanical properties.
[0032] According to a preferred embodiment of the present invention, preferably, the electrolyte comprises N layers of staggered A layers and B layers, N being 2-10 layers, preferably 3-5 layers. The solid electrolyte having the above structure has the advantages of good contact with the electrode and high conductivity.
[0033] According to a preferred embodiment of the present invention, preferably, the A layer material and the B layer material each contain a polymer and an alkali metal salt, and the B layer material contains an inorganic filler; the electrolyte is an AB layer arrangement structure, a BA layer arrangement structure, an ABA layer arrangement structure, a BAB layer arrangement structure, an ABAB layer arrangement structure, a BABA layer arrangement structure, an ABABA layer arrangement structure, a BABAB layer arrangement structure, an ABABAB layer arrangement structure or a BABAABA layer arrangement structure.
[0034] In the present invention, the polymer type can be selected in a wide range. According to a preferred embodiment of the present invention, the polymer is selected from one or more of polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), and poly(vinylidene fluoride hexafluoropropylene); preferably, the polymer is selected from one or more polyethylene oxide (PEO) with a molecular weight of 40W, 60W, 80W, and 100W. The aforementioned preferred embodiment has the advantages of good mechanical properties and high electrical conductivity.
[0035] In the present invention, the alkali metal salt can be selected from a wide range of types. For the present invention, the alkali metal salt includes but is not limited to one or more of lithium salt, sodium salt, potassium salt; for the present invention, lithium salt is preferred; more preferably, the lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoroformimide) (LiTFSI) and lithium perchlorate (LiClO4). The above preferred embodiment has the advantages of good solubility and high ionic conductivity.
[0036] In the present invention, the inorganic filler has a wide range of optional types. For the present invention, the inorganic filler preferably includes but is not limited to aluminum oxide (Al2O3), silicon dioxide (SiO2) and Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 (LLZTO) or more. The above preferred embodiment has the advantages of high strength and high ion conductivity.
[0037] The solid electrolytes having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to the present invention, a method for preparing a solid electrolyte is provided, wherein the method comprises:
[0038] a) forming a slurry M with a polymer and an alkali metal salt;
[0039] b) forming a slurry N with the polymer, the alkali metal salt and the inorganic filler;
[0040] c) coating slurry M or slurry N into a film and heating until the solvent evaporates; coating another layer of different slurry at a fixed point on the surface of the film, maintaining the fixed position and then scraping the slurry flat, and heating until the solvent evaporates; optionally, repeating the fixed-point coating, fixed-point maintenance and scraping of another layer of slurry and heating until the solvent evaporates as needed; so that the electrolyte includes a staggered multilayer structure.
[0041] In the present invention, the optional range of polymer types is relatively wide. For the present invention, according to a preferred embodiment of the present invention, in slurry M and slurry N, the polymer is selected from one or more of polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate (PMMA), polyacrylonitrile (PAN) and poly(vinylidene fluoride hexafluoropropylene); preferably, the polymer is selected from one or more of polyethylene oxide (PEO) having a molecular weight of 40W, 60W, 80W and 100W.
[0042] In the present invention, the types of the alkali metal salts can be selected from a wide range. For the present invention, in slurry M and slurry N, the alkali metal salts each include but are not limited to one or more of sodium salts, potassium salts and lithium salts; preferably lithium salts; more preferably, the lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoroformimide) (LiTFSI) and lithium perchlorate (LiClO4).
[0043] In the present invention, there is no special requirement for the solvent of the slurry. For the present invention, preferably, in the slurry M and the slurry N, the solvent is each selected from one or more of acetonitrile and N,N-dimethylacetamide.
[0044] In the present invention, the inorganic filler has a wide range of optional types. For the present invention, the inorganic filler preferably includes but is not limited to aluminum oxide (Al2O3), silicon dioxide (SiO2) and Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 (LLZTO) or more.
[0045] In the present invention, the optional range of the content of each substance in the slurry M is relatively wide. For the present invention, preferably, the content of the polymer in the slurry M is 0.05-0.1 g / mL; the content of the alkali metal salt is 0.03-0.05 g / mL. The above preferred embodiment has the advantages of good solubility and high ion conductivity.
[0046] In the present invention, the optional range of the content of each substance in the slurry N is relatively wide. For the present invention, preferably, in the slurry N, the content of the polymer is 0.05-0.1 g / mL; the content of the inorganic filler is 0.01-0.04 g / mL; and the content of the alkali metal salt is 0.03-0.05 g / mL.
[0047] In the present invention, there is no special requirement for the scraping method. According to the present invention, the thickness of the scraper used for scraping is preferably 800-1200 μm. The above preferred embodiment has the advantages of suitable thickness and good mechanical properties.
[0048] In the present invention, preferably, the fixed point holding time is preferably 5-10 minutes. The above preferred embodiment has the advantage of uniform pore formation.
[0049] According to a preferred embodiment of the present invention, the method of fixed-point coating is to apply a layer of slurry with a thickness of 2-4 cm on the dry film every 2-4 cm. The above preferred embodiment has the advantages of uniform film formation and uniform pore size distribution.
[0050] In the present invention, there is no special requirement for the method and steps of heating until the solvent evaporates. According to a preferred embodiment of the present invention, the heating method for heating until the solvent evaporates is vacuum drying, the heating temperature is 40-60° C., and the heating time is 24-48 hours.
[0051] According to a preferred embodiment of the present invention, preferably, the following steps are included:
[0052] A) dissolving polyethylene oxide and lithium salt in an organic solvent and stirring at room temperature until completely dissolved;
[0053] Preferably, the molecular weight of the ethylene oxide is 40-100W;
[0054] Preferably, the lithium salt is one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoroformimide) (LiTFSI) and lithium perchlorate (LiClO4);
[0055] Preferably, the organic solvent is one of acetonitrile and N,N-dimethylacetamide;
[0056] B) dissolving polyethylene oxide and lithium salt in an organic solvent, and after they are completely dissolved, adding an inorganic filler therein, and stirring at room temperature until they are uniformly dispersed;
[0057] Preferably, the molecular weight of the ethylene oxide is 40-100W;
[0058] Preferably, the inorganic filler is aluminum oxide (Al2O3), silicon dioxide (SiO2) and Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 (LLZTO) or more;
[0059] Preferably, the lithium salt is one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoroformimide) (LiTFSI) and lithium perchlorate (LiClO4);
[0060] Preferably, the organic solvent is one of acetonitrile and N,N-dimethylacetamide;
[0061] C) coating the solution in A) uniformly on a tetrafluoroethylene flat plate, and vacuum drying until completely dried to obtain a first layer of dry film;
[0062] Preferably, the uniform coating is performed by scraping with a scraper having a thickness of 800-1200 μm;
[0063] Preferably, the vacuum drying temperature is 40-60°C and the heating time is 24-48h;
[0064] D) coating a layer of the solution in B) on the dry film in C) at a fixed point, vacuum drying until the solvent is completely dried, and then coating a layer of the solution in A) at a fixed point, vacuum drying until the solvent is completely dried, to obtain a porous sandwich structure solid electrolyte membrane;
[0065] Preferably, the fixed-point overlay coating is performed by coating a layer of wet film with a thickness of 2-4 cm on the dry film every 2-4 cm, leaving it for 5-10 minutes, and then scraping it flat with a 800-1200 μm scraper;
[0066] Preferably, the vacuum drying temperature is 40-60°C and the heating time is 24-48h;
[0067] E) Assembling the three-layer porous solid electrolyte membrane described in D) with a lithium sheet and a lithium iron phosphate positive electrode sheet into a button cell.
[0068] The above-mentioned method of preparing a sandwich-structured all-solid electrolyte with a special morphology by combining dry and wet processes of the present invention, the obtained solid electrolyte has a pore structure with a pore size distribution of 1-20 μm inside, and is composed of three layers of inner, middle and outer structures, each layer is 50-70 μm thick, and the layers are tightly bonded to each other. From the cross-section, the holes exist independently and do not penetrate each other. In one embodiment, the components of the three-layer membrane are, from top to bottom, PEO-lithium salt, PEO-lithium salt-inorganic filler, and PEO-lithium salt.
[0069] The present invention provides application of the solid electrolyte of the present invention or the solid electrolyte prepared by the method of the present invention in a battery.
[0070] The present invention provides a lithium ion battery, which is assembled from a solid electrolyte, a positive electrode sheet and a lithium sheet. The solid electrolyte is the solid electrolyte described in the present invention or a solid electrolyte prepared by the method described in the present invention.
[0071] According to the present invention, preferably, the positive electrode sheet contains lithium iron phosphate, polyvinylidene fluoride and acetylene black in a mass ratio of 1-50:0.1-10:1, and the current collector is aluminum foil.
[0072] According to a preferred embodiment of the present invention, preferably, the initial discharge capacity of the lithium-ion battery is 160 mAhg -1 above.
[0073] According to a preferred embodiment of the present invention, preferably, the impedance Re of the lithium-ion battery at 60° C. is below 500Ω.
[0074] For ease of understanding of the present invention, the present invention enumerates embodiment as follows. But those skilled in the art should understand that the embodiment is only to help understand the present invention, should not be regarded as specific limitation of the present invention. The endpoints and any value of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values.
[0075] Example 1
[0076] 1. Synthesis of porous sandwich structure solid electrolyte
[0077] 2 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile and magnetically stirred at room temperature for 24 h, which was recorded as solution A.
[0078] 2 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of N,N-dimethylacetamide and stirred magnetically at room temperature for 24 h. Then 0.8 g of Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , and magnetically stirred at room temperature for 24 h, recorded as solution B.
[0079] Take solution A, apply it evenly on a polytetrafluoroethylene plate with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 3cm thick layer of solution B on the dry film every 3cm, leave it for 5min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 3cm thick layer of solution A on the dry film every 3cm, leave it for 5min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h to obtain a porous three-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy. The pore size distribution was 1-20μm, and the thickness of the electrolyte membrane was 1000μm. The mechanical properties of the material were tested by a tensile machine. The tensile rate of the sample was 100mm / min, and the elongation at break was as high as 150%.
[0080] 2. Assembly and testing of all-solid-state lithium-ion batteries
[0081] The above-mentioned synthetic porous electrolyte membrane was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet and a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1). The impedance spectrum of the obtained battery was tested at 60°C, and the test frequency range was: 10 3 -10 6 The Re at 60°C is 367Ω, and the first discharge capacity is 165mAh g at room temperature with a charge and discharge rate of 0.1C.-1 .
[0082] Comparative Example 1
[0083] 1. Synthesis of single-layer solid electrolyte
[0084] 2 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile and stirred magnetically at room temperature for 24 h. Then 0.8 g of Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , magnetically stirred at room temperature for 24 hours, evenly coated on a polytetrafluoroethylene plate with a 1000μm scraper, placed in a vacuum oven, heated at 60℃ for 24 hours, and dried to obtain a single-layer solid electrolyte. The prepared electrolyte membrane was observed for its microscopic morphology using a scanning electron microscope to obtain a porous three-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology using a scanning electron microscope, with no pores and a thickness of 350μm. The mechanical properties of the material were tested using a tensile machine. The tensile rate of the sample was 100mm / min, and the elongation at break was only 80%.
[0085] 2. Assembly and testing of all-solid-state lithium-ion batteries
[0086] The above-mentioned synthetic porous electrolyte membrane was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet and a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1). The Re at 60°C was 800Ω, and the first discharge capacity was 152mAh g at room temperature with a charge and discharge rate of 0.1C. -1
[0087] Figure 1 is a SEM image of the surface of the porous sandwich structure all-solid electrolyte of Example 1. Figure 1 It can be seen that the material consists of pores of different sizes, which is beneficial for ionic conduction;
[0088] Figure 2 This is an enlarged SEM image of the pores on the surface of the porous sandwich structure all-solid electrolyte of Example 1. Figure 2 It can be seen that there are filaments connecting the holes, and the holes are not permeable, which can prevent dendrites from piercing through;
[0089] Figure 3 is a SEM image of the cross section of the porous sandwich structure all-solid electrolyte of Example 1, Figure 3 It can be seen that the cross section is also full of non-penetrating pore structures;
[0090] Figure 4 The impedance spectrum of the lithium battery based on the porous sandwich structure all-solid electrolyte of Example 1 is shown in FIG. Figure 4It can be seen that the Re of the battery assembled with the solid electrolyte decreases with increasing temperature, and is as low as 367Ω at 60°C;
[0091] Figure 5 is a SEM image of the surface of the single-layer all-solid electrolyte of Comparative Example 1, Figure 5 It can be seen that the surface of the single-layer electrolyte is uniform and has a non-porous structure.
[0092] Example 2
[0093] 1. Synthesis of porous sandwich structure solid electrolyte
[0094] 1.5 g of polyacrylonitrile with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile and magnetically stirred at room temperature for 24 h, which was recorded as solution A.
[0095] 1.5 g of polyacrylonitrile with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile, and magnetically stirred at room temperature for 24 h. Then 0.8 g of Al2O3 was added, and magnetically stirred at room temperature for 24 h. This was recorded as solution B.
[0096] Take solution B, apply it evenly on a polytetrafluoroethylene plate with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a layer of 3cm thick solution A on the dry film every 2cm, leave it for 5min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a layer of 3cm thick solution B on the dry film every 2cm, leave it for 5min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h to obtain a porous three-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy to obtain a porous three-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy. The pore size distribution of the pores was 1-20μm, and the thickness of the electrolyte membrane was 650μm. The mechanical properties of the material were tested by a tensile machine. The tensile rate of the sample was 100mm / min, and the elongation at break was as high as 135%.
[0097] 2. Assembly and testing of all-solid-state lithium-ion batteries
[0098] The above-mentioned synthetic porous electrolyte membrane was used as electrolyte and assembled into a 2035 button cell with a lithium sheet and a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1). The impedance spectrum of the obtained battery was tested at 30, 40, 50, 60, and 70°C, respectively, and the test frequency range was: 10 3 -10 6 Ω, Re at 60°C is 412Ω. At room temperature, the charge and discharge rate is 0.1C, and the first discharge capacity is 161mAh g-1 .
[0099] Example 3
[0100] 1. Synthesis of porous sandwich structure solid electrolyte
[0101] 1.0 g of polyvinylidene fluoride with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile and magnetically stirred at room temperature for 24 h, which was recorded as solution A.
[0102] 1.0 g of polyvinylidene fluoride with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile, and magnetically stirred at room temperature for 24 h. Then 0.7 g of SiO2 was added, and magnetically stirred at room temperature for 24 h. This was recorded as solution B.
[0103] Take solution A, apply it evenly on a polytetrafluoroethylene plate with an 800μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 3cm thick layer of B solution every 3cm on the dry film, leave it for 5min, scrape it flat with an 800μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 3cm thick layer of A solution every 3cm on the dry film, leave it for 5min, scrape it flat with an 800μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 3cm thick layer of B solution every 3cm on the dry film, leave it for 5min, scrape it flat with an 800μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h, and then obtain a porous four-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy, and the pore size distribution of the holes was 1-20μm and the thickness was 1100μm. The mechanical properties of the material were tested using a tensile machine. The tensile rate of the sample was 100 mm / min, and the elongation at break was as high as 137%.
[0104] 2. Assembly and testing of all-solid-state lithium-ion batteries
[0105] The above-mentioned synthetic porous electrolyte membrane was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet and a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1). The impedance spectrum of the obtained battery was tested at 60°C, and the test frequency range was: 10 3 -10 6 Ω, Re at 60°C is 450Ω. At room temperature, the charge and discharge rate is 0.1C, and the first discharge capacity is 164mAh g -1 .
[0106] Example 4
[0107] 1. Synthesis of porous sandwich structure solid electrolyte
[0108] 1.0 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile and magnetically stirred at room temperature for 24 h, which was recorded as solution A.
[0109] 1.0 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile and stirred magnetically at room temperature for 24 h. Then 0.7 g of Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , and magnetically stirred at room temperature for 24 h, recorded as solution B.
[0110] Take solution A, apply it evenly on a polytetrafluoroethylene plate with an 800μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 3cm thick layer of B solution every 3cm on the dry film, leave it for 5min, scrape it with an 800μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 3cm thick layer of B solution every 3cm on the dry film, leave it for 5min, scrape it with an 800μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 3cm thick layer of A solution every 3cm on the dry film, leave it for 5min, and scrape it with an 800μm scraper to obtain a porous four-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy, and the pore size distribution of the holes was 1-20μm and the thickness was 1100μm. The mechanical properties of the material were tested using a tensile machine. The tensile rate of the sample was 100 mm / min, and the elongation at break was 110%.
[0111] 2. Assembly and testing of all-solid-state lithium-ion batteries
[0112] The above-mentioned synthetic porous electrolyte membrane was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet and a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1). The impedance spectrum of the obtained battery was tested at 60°C, and the Re at 60°C was 500Ω; the test frequency range was: 10 3 -10 6 Ω. At room temperature, the charge and discharge rate was 0.1C, and the first discharge capacity was 161 mAh g -1 .
[0113] Example 5
[0114] 1. Synthesis of porous sandwich structure solid electrolyte
[0115] 2 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile and magnetically stirred at room temperature for 24 h, which was recorded as solution A.
[0116] 2 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile and stirred magnetically at room temperature for 24 h. Then 0.8 g of Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , and magnetically stirred at room temperature for 24 h, recorded as solution B.
[0117] Take solution A, apply it evenly on a polytetrafluoroethylene plate with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 5cm thick layer of solution B on the dry film every 5cm, leave it for 3min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 5cm thick layer of solution A on the dry film every 5cm, leave it for 3min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h to obtain a porous three-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy. The pore size distribution of the holes was 1-20μm and the thickness was 1000μm. The mechanical properties of the material were tested by a tensile machine. The tensile rate of the sample was 100mm / min, and the elongation at break was as high as 100%.
[0118] 2. Assembly and testing of all-solid-state lithium-ion batteries
[0119] The above-mentioned synthetic porous electrolyte membrane was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet and a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1). The impedance spectrum of the obtained battery was tested at 60°C, and the test frequency range was: 10 3 -10 6 The Re at 60°C is 600Ω. When charged and discharged at a rate of 0.1C at room temperature, the first discharge capacity is 155mAh g -1 .
[0120] Example 6
[0121] 1. Synthesis of porous sandwich structure solid electrolyte
[0122] 2 g of polyethylene oxide with a molecular weight of 30 W and 1 g of lithium bis(fluorosulfonyl)imide (LiTFSI) were dissolved in 20 mL of acetonitrile and magnetically stirred at room temperature for 24 h, which was recorded as solution A.
[0123] 2 g of 60 W polyethylene oxide and 1 g of lithium bis(fluorosulfonyl)imide (LiTFSI) were dissolved in 20 mL of acetonitrile and stirred magnetically at room temperature for 24 h. 0.8 g of Li 6.4 Ln3Z 1.4 Ta0.6 O 12 , and magnetically stirred at room temperature for 24 h, recorded as solution B.
[0124] Take solution A, apply it evenly on a polytetrafluoroethylene plate with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 3cm thick layer of solution B on the dry film every 3cm, leave it for 5min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a 3cm thick layer of solution A on the dry film every 3cm, leave it for 5min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h to obtain a porous three-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy, and it had a non-penetrating pore structure. A porous three-layer membrane was obtained. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy, and the pore size distribution of the pores was 1-20μm and the thickness was 1000μm. The mechanical properties of the material were tested using a tensile machine. The tensile rate of the sample was 100 mm / min, and the elongation at break was as high as 110%.
[0125] 2. Assembly and testing of all-solid-state lithium-ion batteries
[0126] The above-mentioned synthetic porous electrolyte membrane was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet and a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1). The impedance spectrum of the obtained battery was tested at 60°C, and the test frequency range was: 10 3 -10 6 The Re at 60°C is 408Ω. The first discharge capacity is 162mAh g at room temperature with a charge and discharge rate of 0.1C. -1 .
[0127] Example 7
[0128] 1. Synthesis of porous sandwich structure solid electrolyte
[0129] 2 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile and magnetically stirred at room temperature for 24 h, which was recorded as solution A.
[0130] 2 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of N,N-dimethylacetamide and stirred magnetically at room temperature for 24 h. Then 0.8 g of Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , and magnetically stirred at room temperature for 24 h, recorded as solution B.
[0131] Take solution A, apply it evenly on a polytetrafluoroethylene plate with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a layer of 1cm thick B solution every 1cm on the dry film, leave it for 5min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a layer of 1cm thick A solution every 1cm on the dry film, leave it for 5min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h to obtain a porous three-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy to obtain a porous three-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy, and there was no pore size distribution. The thickness is 1000μm. The mechanical properties of the material were tested by a tensile machine. The tensile rate of the sample was 100mm / min, and the elongation at break was 100%.
[0132] 2. Assembly and testing of all-solid-state lithium-ion batteries
[0133] The above-mentioned synthetic porous electrolyte membrane was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet and a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1). The impedance spectrum of the obtained battery was tested at 60°C, and the test frequency range was: 10 3 -10 6 The Re at 60°C is 605Ω. The first discharge capacity is 156mAh g at room temperature with a charge and discharge rate of 0.1C. -1 .
[0134] Comparative Example 2
[0135] 1. Synthesis of porous sandwich structure solid electrolyte
[0136] 2 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of acetonitrile and magnetically stirred at room temperature for 24 h, which was recorded as solution A.
[0137] 2 g of polyethylene oxide with a molecular weight of 40 W and 1 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 20 mL of N,N-dimethylacetamide and stirred magnetically at room temperature for 24 h. Then 0.8 g of Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , and magnetically stirred at room temperature for 24 h, recorded as solution B.
[0138] Take solution A, use a 1000μm scraper to evenly coat it on a polytetrafluoroethylene plate, put it in a vacuum oven, and heat it at 60℃ for 24h; then apply a layer of solution B on the dry film, place it for 5min, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h; after drying, apply a layer of solution A on the dry film, scrape it flat with a 1000μm scraper, put it in a vacuum oven, and heat it at 60℃ for 24h to obtain a three-layer membrane. The prepared electrolyte membrane was observed for its microscopic morphology by scanning electron microscopy, and there was no porous structure. The mechanical properties of the material were tested by a tensile machine. The tensile rate of the sample was 100mm / min, and the elongation at break was 82%.
[0139] 2. Assembly and testing of all-solid-state lithium-ion batteries
[0140] The above-mentioned synthetic porous electrolyte membrane was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet and a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1). The impedance spectrum of the obtained battery was tested at 60°C, and the test frequency range was: 10 3 -10 6 The Re at 60°C is 620Ω. The first discharge capacity is 157mAh g at room temperature with a charge and discharge rate of 0.1C. -1 .
[0141] The embodiments of the present invention are only used to illustrate the detailed process of the present invention, but the present invention is not limited to the above process, that is, the present invention can be implemented without relying on the steps described in the above embodiments. In summary, any improvements made by those skilled in the art to the present invention, including replacement of the raw materials and additives described in the present invention, selection of specific implementation methods, etc., all belong to the protection scope and disclosure scope of the present invention.
Claims
1. A solid electrolyte, characterized in that The electrolyte comprises an A layer and a B layer which are arranged alternately. The A layer material is different from the B layer material. The A layer material and the B layer material respectively contain a polymer and an alkali metal salt. One of the A layer material and the B layer material contains an inorganic filler.
2. The electrolyte according to claim 1, wherein The solid electrolyte and the lithium iron phosphate electrode sheet are assembled into a battery with an initial discharge capacity of 160 mAh g -1 above; and / or The impedance Re at 60° C. of a battery assembled with the solid electrolyte and the lithium iron phosphate electrode sheet is below 500Ω, preferably 300-500Ω; and / or The tensile elongation at break of the solid electrolyte is above 100%, preferably 100-150%; and / or The thickness of the solid electrolyte is 900-2000 μm.
3. The electrolyte according to claim 1 or 2, wherein The solid electrolyte has a plurality of pores, each of which exists independently and has an irregular shape, and the pores do not penetrate the layer structure of the electrolyte, and preferably the pore size of the pores is 1-20 μm; Preferably, the holes have filamentous morphology running through them; and / or The electrolyte comprises N layers of A layers and B layers arranged alternately, N being 2-10 layers, preferably 3-5 layers; Preferably, the A layer material and the B layer material each contain a polymer and an alkali metal salt, and the B layer material contains an inorganic filler; the electrolyte is an AB layer arrangement structure, a BA layer arrangement structure, an ABA layer arrangement structure, a BAB layer arrangement structure, an ABAB layer arrangement structure, a BABA layer arrangement structure, an ABABA layer arrangement structure, a BABAB layer arrangement structure, an ABABAB layer arrangement structure or a BABAABA layer arrangement structure.
4. The electrolyte according to any one of claims 1 to 3, wherein The polymer is selected from one or more of polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, polyacrylonitrile and poly(vinylidene fluoride hexafluoropropylene); Preferably, the polymer is selected from polyethylene oxide having a molecular weight of one or more of 40W, 60W, 80W and 100W; and / or The alkali metal salt is selected from one or more of sodium salt, potassium salt and lithium salt; preferably lithium salt; more preferably, the lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoroformimide) and lithium perchlorate; and / or Inorganic fillers are alumina, silica and Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 One or more of .
5. A method for preparing a solid electrolyte, wherein: The method includes: a) forming a slurry M with a polymer and an alkali metal salt; b) forming a slurry N with the polymer, the alkali metal salt and the inorganic filler; c) coating slurry M or slurry N into a film and heating until the solvent evaporates; coating another layer of different slurry at a fixed point on the surface of the film, maintaining the fixed position and then scraping the slurry flat, and heating until the solvent evaporates; optionally, repeating the fixed-point coating, fixed-point maintenance and scraping of another layer of slurry and heating until the solvent evaporates as needed; so that the electrolyte includes a staggered multilayer structure.
6. The preparation method according to claim 5, wherein: In slurry M and slurry N, The polymer is selected from one or more of polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, polyacrylonitrile and poly(vinylidene fluoride hexafluoropropylene); Preferably, the polymer is selected from polyethylene oxide having a molecular weight of one or more of 40W, 60W, 80W and 100W; and / or The alkali metal salts are each selected from one or more of sodium salts, potassium salts and lithium salts; preferably lithium salts; more preferably, the lithium salts are selected from one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoroformimide) and lithium perchlorate; The solvents are each selected from one or more of acetonitrile and N,N-dimethylacetamide; and / or The inorganic filler is selected from alumina, silica and Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 One or more of .
7. The preparation method according to claim 5 or 6, wherein: In the slurry M, the content of the polymer is 0.05-0.1 g / mL; the content of the alkali metal salt is 0.03-0.05 g / mL; In slurry N, the content of polymer is 0.05-0.1 g / mL; the content of inorganic filler is 0.01-0.04 g / mL; and the content of alkali metal salt is 0.03-0.05 g / mL.
8. The method according to any one of claims 5 to 7, wherein: The thickness of the scraper used for scraping is 800-1200μm; The fixed point holding time is 5-10 minutes; The method of spot coating is to apply a layer of slurry with a thickness of 2-4cm every 2-4cm on the dry film; The heating method for heating until the solvent evaporates is vacuum drying, the heating temperature is 40-60°C, and the heating time is 24-48h.
9. Use of the solid electrolyte described in any one of claims 1 to 4 or the solid electrolyte prepared by the method described in any one of claims 5 to 8 in a battery.
10. A lithium ion battery, characterized in that: The battery is assembled from a solid electrolyte, a positive electrode sheet and a lithium sheet, wherein the solid electrolyte is a solid electrolyte as described in any one of claims 1 to 4 or a solid electrolyte prepared by the method as described in any one of claims 5 to 8; Preferably, the positive electrode sheet contains a mass ratio of 1-50: 0.1-10:1 lithium iron phosphate, polyvinylidene fluoride and acetylene black, the current collector is aluminum foil; Preferably, the initial discharge capacity of the lithium-ion battery is 160 mAh g -1 above; Preferably, the impedance Re of the lithium ion battery at 60° C. is less than 500Ω.
Citation Information
Patent Citations
Solid electrolyte membrane, preparation method of solid electrolyte membrane, and lithium ion battery
CN107403954A
High voltage-resistant multi-stage structure composite solid-state electrolyte for lithium battery
CN107732297A
Composite positive electrode and application of composite positive electrode in solid-state polymer lithium ion battery
CN110085805A
Asymmetric solid electrolyte, preparation method thereof and application thereof in high-voltage solid-state battery
CN111276738A
Composite solid electrolyte, all-solid-state lithium ion battery and preparation method of all-solid-state lithium ion battery
CN111697262A